Substrate-orientation dependence of β-Ga2O3 (100), (010), (001), and (2¯01) homoepitaxy by indium-mediated metal-exchange catalyzed molecular beam epitaxy (MEXCAT-MBE) - P. Mazzolini; A. Falkenstein; C. Wouters; R. Schewski; T. Markurt; Z. Galazka; M. Martin; M. Albrecht; O. Bierwagen (APL Materials, 2020)
We experimentally demonstrate how In-mediated metal-exchange catalysis (MEXCAT) allows us to widen the deposition window for β-Ga2O3 homoepitaxy to conditions otherwise prohibitive for its growth via molecular beam epitaxy (e.g., substrate temperatures ≥800 °C) on the major substrate orientations, i.e., (010), (001), (2¯01), and (100) 6°-offcut. The obtained crystalline qualities, surface roughnesses, growth rates, and In-incorporation profiles are shown and compared with different experimental techniques. The growth rates, Γ, for fixed growth conditions are monotonously increasing with the surface free energy of the different orientations with the following order: Γ(010) > Γ(001) > Γ(2¯01) > Γ(100). Ga2O3 surfaces with higher surface free energy provide stronger bonds to the surface ad-atoms or ad-molecules, resulting in decreasing desorption, i.e., a higher incorporation/growth rate. The structural quality in the case of (2¯01), however, is compromised by twin domains due to the crystallography of this orientation. Notably, our study highlights β-Ga2O3 layers with high structural quality grown by MEXCAT-MBE not only in the most investigated (010) orientation but also in the (100) and (001) ones. In particular, MEXCAT on the (001) orientation results in both growth rate and structural quality comparable to the ones achievable with (010), and the limited incorporation of In associated with the MEXCAT deposition process does not change the insulating characteristics of unintentionally doped layers. The (001) surface is therefore suggested as a valuable alternative orientation for devices.